Z-Plasty Made Simple - Sumaira Z. Aasi (Dermatology Research and Practice)
A Z-plasty is a critical and reliable technique that is useful for scar revisions and correction of free margin distortion. A Z-plasty can help lengthen a contracted scar, change the direction of a scar so that it is better aligned with the relaxed skin tension lines, or interrupt and break a scar for better camouflage. This article will review the technique of a basic Z-plasty as well as provide case examples of its use in free margin distortion and scar revision.